2015
DOI: 10.1016/j.ijgo.2015.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Regret following female sterilization in Slovenia

Abstract: Few women report regret after tubal sterilization in Slovenia. However, an additional consultation on post-sterilization problems and depressive disorder before sterilization might minimize the risk of regret.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…However, little is known about the topic in Japanese women, and also there are almost no report regarding regret about not receiving permanent contraception. Previous study showed the proportion of women with self‐reported regret about receiving permanent contraception as 1.3%–28% 12–17 . The present study found that 13% of women with permanent contraception expressed self‐reported regret in line with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…However, little is known about the topic in Japanese women, and also there are almost no report regarding regret about not receiving permanent contraception. Previous study showed the proportion of women with self‐reported regret about receiving permanent contraception as 1.3%–28% 12–17 . The present study found that 13% of women with permanent contraception expressed self‐reported regret in line with the findings of previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…For women over the age of 30, the overall probability was 5.9%, with a figure of 5.4% for child-free women 17. Finally, in a study of Slovenian women, Becner et al 18 report that out of 308 women only 4 (1.3%) reported regret about being sterilised. Based on such findings, Curtis et al 19 conclude that ‘most women who undergo sterilization remain satisfied with their choice of a permanent method of contraception’.…”
Section: Autonomy and Future Regretmentioning
confidence: 97%
“…Dari sebuah penelitian didapatkan bahwa sekitar 1-3% wanita yang melakukan sterilisasi berkeinginan untuk memiliki anak kembali di kemudian hari. 1 Wanita yang ingin memiliki anak kembali setelah sterilisasi dihadapkan pada dua pilihan, yaitu reanastomosis atau rekanalisasi tuba dan prosedur in vitro fertilization (IVF). 2 Namun, teknologi reproduksi berbantuan melalui IVF ini dinilai sebagai pilihan mahal sedangkan rekanalisasi tuba mungkin pilihan terjangkau, terutama untuk negara berkembang seperti Indonesia.…”
Section: Pendahuluanunclassified